Cold active enzyme and method thereof - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Mohamad Ali, Mohd Shukuri (2014)
The objective of the present invention is to obtain a low temperature producing enzyme and more particularly, the enzyme provides a bifunctional purpose of varying its enzyme activity into activity of another enzyme. The present invention has overcome problems such as ability of obtaining an enzyme at low temperature.